Rancang Bangun Sistem Informasi Data Warehouse Produk Elektronik Menggunakan Metode Waterfall dengan Analisa PIECES Berbasis Web : Studi Kasus: PT.Karlin Mastrindo - Firdan Febrian (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
An information system is a series that includes aspects of software, hardware and brainware in a structured manner with performance in a process that is interconnected so as to create a certain desired product, then the development of website-based system infrastructure can make it easier to data warehouse electronic products for both incoming and outgoing goods. for the admin, however, from the ongoing data warehouse process there are several problematic factors that influence it, namely, electronic product warehouse data collection for incoming and outgoing goods still uses a simple Microsoft Excel format which takes a long time and there are many warehouse data collection archives on computer storage as reports so it is vulnerable to viruses.